Modo de afrontamiento al estrés en adolescentes mujeres - Quezada Zevallos, Jenny (2006)
Research of a simple descriptive type is informed. The sample was formed by 172 female students, between 16 and 18 years of age with concluded secondary studies, from different districts of Lima Metropolitan, admitted to a private university. The instrument employed was COPE by Carver, CH. & Scheier, M. (1989). It was found that the most used way to face stress concern strategies that Focus the Problem.